Study on the Attitudes and Knowledge of Teachers and Future Teachers about Immediate Health Care Measures at School - Paula Pais-Roldán; María del Carmen Olmos-Gómez; Jesús Manuel Cuevas-Rincón; Mónica Luque-Suárez (MDPI AG, 2022)
The level and need for immediate health care measures training for teachers are of growing concern for two main reasons: on the one hand, these contents are part of the school curriculum and, on the other hand, teachers are the first adults to intervene in case of school injury. However, in Spain, first aid (FA) does not appear as obligatory content in the university training of teachers. The aim of the present study was to design and validate a questionnaire on the attitude of pre-school and primary school teachers towards first aid knowledge adapted to the school context and to analyze its psychometric properties. First of all, the psychometric values of the questionnaire were tested: through its validation and reliability. Subsequently, a correlation study was carried out as well as a logistic regression in order to know the knowledge and attitudes of teachers and future teachers about the importance of the Immediate Attention Measures at school. The sample consisted of 392 participants: active teachers (71%) and future teachers (29%, the latter being final year students) of the infant and primary stages from the northern, central and southern areas of Spain. The results show adequate psychometric values, establishing three factors: attitude towards general knowledge in FA and learning methodology; attitude towards wounds and CPR algorithm (most frequent and/or serious events); self-perception of knowledge or skill in FA. Pearson's correlation test identified significant values (p < 0.01) and positive association between Factors 1 and 2 (r = 0.422) and between 1 and 3 (0.244). The conclusions of the results of the validation process of the questionnaire on the attitude of teachers and future teachers to knowledge for immediate health care measures training are valid and reliable to an acceptable degree. Regression study demonstrates the importance of including first aid training in teachers' degrees.